Comparative microbial antibiotic resistome between urban and deep forest environments. Issue 4 (10th March 2021) - Zheng, Yongchang; Yu, Si; Wang, Guanqun; Xie, Fucun; Xu, Haifeng; Du, Shunda; Zhao, Haitao; Sang, Xinting; Lu, Jizhou; Jiang, Wenjun
Summary: A paradoxical result of using antibiotics to eradicate microbial pathogens is the emergence of a vast number of resistant microbes in various environments. The concern that environmental microbes will inevitably become resistant to virtually every clinically usable antibiotics has been exacerbated by the spread of these resistance genes across different environments and the emergence of multidrug resistant phenotypes. Here, we provide metagenomic insights into the microbiomes and resistomes of 16 soil samples collected from hospitals, residential areas, and forest parks in the megacity of Beijing and deep forests in the Yunnan province. Using Illumina HiSeq sequencing, we investigated the microbial diversity within the metagenomic shotgun reads and identified 486 antibiotic‐resistant genes (ARGs) classified into 30 types from these samples, among which multidrug resistance genes were the most abundant. Our results present an important reference and direct comparison of microbial antibiotic resistomes of soil samples from a megacity and deep forests and extend our understanding of the spread of ARGs in modern urban and natural environments.